Impact brain apnoea – A forgotten cause of cardiovascular collapse in trauma. (August 2016) - Wilson, Mark H; Hinds, John; Grier, Gareth; Burns, Brian; Carley, Simon; Davies, Gareth
Abstract: Objective: Early death following cranial trauma is often considered unsurvivable traumatic brain injury (TBI). However, Impact Brain Apnoea (IBA), the phenomenon of apnoea following TBI, may be a significant and preventable contributor to death attributed to primary injury. This paper reviews the history of IBA, cites case examples and reports a survey of emergency responder experience. Methods: Literature and narrative review and focused survey of pre-hospital physicians. Results: IBA was first reported in the medical literature in 1705 but has been demonstrated in multiple animal studies and is frequently anecdotally witnessed in the pre-hospital arena following human TBI. It is characterised by the cessation of spontaneous breathing following a TBI and is commonly accompanied by a catecholamine surge witnessed as hypertension followed by cardiovascular collapse. This contradicts the belief that isolated traumatic brain injury cannot be the cause of shock, raising the possibility that brain injury may be misinterpreted and therefore mismanaged in patients with isolated brain injury. Current trauma management techniques (e.g. rolling patients supine, compression only cardiopulmonary resuscitation) could theoretically compound hypoxia and worsen the effects of IBA. Anecdotal examples from clinicians attending head injured patients within a few minutes of injury are described. Proposals for the study and intervention for IBA using advances in remote technology are discussed. Conclusion: IBA is a potential cause of early death in some head injured patients. The precise mechanisms in humans are poorly understood but it is likely that early, simple interventions to prevent apnoea could improve clinical outcomes.